Evaluasi Pengelolaan Alokasi Dana Desa Untuk Pembangunan Sarana Prasarana Desa (Desa Wonoasri Kecamatan Grogol Kabupaten Kediri) - Wibowo, Gunawan Arif (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
Allocation of village fund is a balancing fund of the central government to village which fund intended to improve the distribution of development in the village include for infrastructure development Wonoasri Village, Grogol, Kediri. The purpose of this study was to assess the management of allocation of village fund for infrastructure development Wonoasri Village, Grogol, Kediri.The methodology of this study used a qualitative descriptive by involving participants from the village government and the community. Collecting data in this study using the method of documentation, observation and interviews. Analysis in this study using a Logical Framework Analisys. Results of this study were 1) allocation of village fund is divided into 30% for the BPD government activities and 70% for community development activities. The allocation of funds for rural development activities by 70% over 40% for physical development and 30% is used for village institutions. 2) Stakeholders involved in the allocation of village fund include : kepala desa, sekretaris desa, Kaur Keuangan, Ketua LPMD. 3) In the development of infrastructure Wonoasri an error in the post budget, the proposal is not acommodation, planning the allocation of the village fund does not take into consideration the period of tenure of the head of the village as well as planning which resulted in an adjustment of the details of expenditure on the implementation of the development. 4)there are supporting factors the management of village fund allocation include: legislation, supervisors in the management of the allocation of village funds. While the inhibiting factors of management allocation of village fund includes limited of funds to allocated rural development of village infrastructure, and not use RPJMDes as guideline to infrastructure development program.